Warburg's "Goddess in Exile": The "Nymph" Fragment between Letter and Taxonomy, Read with Heinrich Heine. Issue 3 (5th December 2013) - Weigel, Sigrid
Abstract : As regards Aby Warburg's oeuvre, it is fascinating that three unfinished or unpublished projects have come to represent the very theorems now appearing of most interest for cultural historians and theorists: The Mnemosyne Atlas representing pictorial memory; the Serpent Ritual as theorem for a cultural-anthropological reading of pagan cultures; and the Nymph Fragment as a foundational figure of modern iconology. This essay undertakes an analysis of the fragmentary character of Warburg's way of working, arguing that his search for an analytic model to account for the interplay between Christian and pagan/polytheistic traditions displays striking asynchronies and displacements. Rather than explicating these irregularities biographically, the conceptual problems tied to his methods and cognitive interests are investigated. The article thus examines a set of conceptual questions whose relevance extends well past Warburg's methodology, considering the dimensions of religious and cultural-historical theory within a broader history of European arts and media. Concentrating on probably the most cited figure from Warburg's repertoire of images, the "nymph" figure on Ghirlandaio's fresco The Birth of St John the Baptist, the essay focuses on Warburg's borrowings from Heinrich Heine and reveals Heine to be a blind spot in research on Warburg up until now.